Was this a Bilateral Testicular Torsion? Dilemma of a Paediatric Surgeon-Case Report - Nogalska, Sonia; Polok, Marcin; ?ukawska, Agata; Rasiewicz, Marcin; Bag?aj, Maciej (Archives of Clinical and Medical Case Reports, 2020)
Abstract not available in the source database.